Nachhaltige Finanzmärkte: Finanztransaktionssteuer und hohe Eigenkapitalpuffer sind unverzichtbar - Dorothea Schäfer (DIW Wochenbericht, 2013)
Nachhaltigkeit der Finanzmärkte ist eine Forderung, die erst in allerjüngster Zeit auf der wirtschaftspolitischen Agenda aufgetaucht ist. Hingegen ist die Stabilität des Finanzsystems ein seit Jahrzehnten angestrebtes Ziel. Das Verhältnis von Nachhaltigkeit und Stabilität ist indes noch ungeklärt. Angelehnt an das im Umweltbereich geltende Leitbild der Nachhaltigkeit werden hier Anforderungen an nachhaltige Finanzmärkte formuliert. Finanzmarktstabilität ist als öffentliches Gut zu begreifen. Internalisierung der Nutzungskosten, ausreichende Pufferbildung bei Finanzinstituten, um von selbst und ohne Hilfe des Steuerzahlers wieder zur Stabilität zurückkehren zu können, Vielfalt, Langfristorientierung und Glaubwürdigkeit bilden die Voraussetzung für die Nachhaltigkeit der Finanzmärkte. Die Finanztransaktionssteuer und eine auf die Bilanzsumme bezogene Eigenkapitalquote (Leverage Ratio) sind elementare Bausteine dieses Nachhaltigkeitskonzepts. – – The sustainability of the financial markets is a requirement that has only appeared very recently on the economic policy agenda, whereas a stable financial system has been a declared goal for decades. The relationship between sustainability and stability is, however, still unclear. The two terms are often used synonymously but stability is only one part of sustainability. The following outlines the requirements for sustainable financial markets based on the current general principles of environmental sustainability. Financial stability is considered a public good. The prerequisites for the sustainability of financial markets include internalizing costs of use, financial institutions forming adequate buffers in order to restore stability autonomously and without the help of the taxpayer, diversity, a long-term outlook, and credibility. In this concept of sustainability, there is room for a financial transaction tax and a higher leverage ratio; both are cornerstones of the planned restructuring of the financial markets.
Keywords: G20; 330; sustainable financial architecture; financial transaction tax; leverage ratio